Effects of food processing and fibre content on the digestibility, energy intake and biochemical parameters of Blue-and-gold macaws (Ara ararauna L. - Aves, Psittacidae) - Veloso, R. R.; Sakomura, N. K. [UNESP]; Kawauchi, I. M. [UNESP]; Malheiros, E. B. [UNESP]; Carciofi, A. C. [UNESP] (Wiley-Blackwell, 2014)
Considering the increased incidence of obesity and metabolic diseases in caged psittacines, the effect of fibre and food processing was evaluated in the Blue-and-gold macaw. Four food formulations (0%, 7%, 14% and 21% of sugarcane fibre) processed by pelleting or extrusion were studied, resulting in eight diets. To study digestibility, 48 macaws housed in pairs in cages was used in a block design. Subsequently, diets containing 0% or 21% sugarcane fibre, pelleted or extrude was fed for 4months to evaluate energy intake and blood metabolites. A 2x2x2 (two fibre levels, two food processing methods and two genders) factorial arrangement with subplots (beginning and end) was used. When differences were detected in anova's F test, data were submitted to polynomial contrasts in the first experiment and to orthogonal contrasts in the second experiment (p<0.05). Fibre addition reduced protein, fat and energy (p<0.001) digestibility in both food processing. Pelleted foods presented higher dry matter digestibility and food metabolisable energy (ME) than the extruded ones (p<0.05). Fibre addition or the type of processing did not change ME ingestion (p>0.05). The macaws gained body weight (p<0.05) regardless of the diet (p>0.05), but females fed with the high-fibre diets did not gain weight (p>0.05), suggesting a low food ME (12.5kJ/g).The substitution of the original diet (sunflower seeds, fruits and cooked maize) by the experimental foods decreased the basal (12-h fast) concentrations of glucose, cholesterol and triglycerides (p<0.001). The consumption of pelleted diets reduced serum glucose and cholesterol (p<0.05). Results suggest that the pelleted diets were more beneficial and can be used to reduce blood metabolites related to metabolic disorders that are commonly observed in macaws.
Keywords: pelletisation; Triglycerides; Energy; Glucose; extrusion